Tanggung Jawab Pemerintah Daerah Kabupaten Banyuwangi atas Pencemaran Lingkungan Akibat Pengolahan Ikan di Muncar - Istiana, Istiana; Gautama Budi Arundhati; Ratih Listyana Chandra (Jurnal Ragam Pengabdian, 2026)
Muncar Subdistrict, Banyuwangi Regency, is known as Indonesia's largest fish-processing industrial center, yet the activities of 49 fish-processing companies operating in the area have caused persistent wastewater pollution due to direct discharge into the environment without adequate Wastewater Treatment Installations (IPAL). This study aims to analyze the responsibility of the Banyuwangi Regency Government for such pollution, efforts to protect the rights of affected communities, and to formulate an ideal concept for future environmental law enforcement. The study employs an empirical juridical method with a sociological legal approach, through observation, interviews, and questionnaires administered to the Environmental Agency, related institutions, and affected communities in Kedungrejo Village, Muncar. The findings indicate that supervision conducted by the Banyuwangi Environmental Agency has not been effective due to limited human resources, minimal transparency, and law enforcement restricted mainly to written warnings. Fish-processing wastewater pollution has degraded water quality, caused health problems, reduced fishermen's catches by up to 60%, and damaged road infrastructure. Environmental restoration and compensation through CSR programs have not been implemented equitably. The study recommends strengthening institutional capacity, applying the polluter-pays principle, and adopting an anticipatory-government approach to achieve fair and sustainable environmental law enforcement.